Research of a mathematical model of low-concentrated aqueous polymer solutions (Abstract and Applied Analysis)
The initial-boundary value problem for the mathematical model of low-concentrated aqueous polymer solutions is considered. For this initial-boundary value problem a concept of a weak solution is introduced and the existence theorem for such solutions is proved.